Pembelajaran al-Qur’an Secara Digital: Pergeseran Sistem Isnad dan Peneguhan Otoritas Baru - Abdul Majit; Miski Miski (Balai Penelitian dan Pengembangan Agama Semarang, 2023)
This research analyzes the phenomenon of changes in the isnad system in learning on the Qur’an on the Qara'a mobile application. This mobile application provides Al-Qur'an learning services that are supported by machine learning and artificial intelligence to correct the user's reciting of the Qur'an so that they have a